THE DEVELOPMENT OF THE JOB OF THE SECRETARIES OF STATE AND THEIR ROLE IN THE EARLY PERIOD OF ISLAM - Mahafzah, Hussain Ali (European Scientific Journal, ESJ, 2012)
This study tried to shed light on the circumstances which led to the rise of writing and the role of secretaries of State from the beginning of the Islamic State at the age of the Prophet (peace may be upon him), the Orthodox Age till the end of the Umayyad Age. This study aimed at revealing the importance of secretaries of state in developing the administration of the Arabic- Islamic State, spreading out its culture and generalizing its political address to reveal the job gradual advance of the secretary of state from an administrative employee to a person who spread out the culture of his age in a way that made him a thinker of the state and its spokesman.